2009
DOI: 10.3724/sp.j.1005.2009.00359
|View full text |Cite
|
Sign up to set email alerts
|

Principle of diversity arrays technology (DArT) and its applications in genetic research of plants

Abstract: Diversity arrays technology (DArT) is a microarray hybridization-based molecular marker technique, and a novel method to discover genetic polymorphic markers. DArT has recently been applied in genetic research of plants because of its characteristics of sequence-independent, high-throughput, fast, low-cost. We briefly introduce the principle, characteristics, protocol of DArT and its application in genetic research of plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Commonly, its key parts are two loop reactors and one or two fluidized bed reactors (FBRs). Among them, the loop reactors are used to produce homopolypropylene, ethylene−propylene random copolymer, and ethylene−propylene−1-butene copolymer, and the FBR is used to produce impact polypropylene. , It is well acknowledged that the loop reactor is one of the best choices for the preparation of homopolypropylene due to its high mixing capability as well as high heat transfer/exchange rate …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, its key parts are two loop reactors and one or two fluidized bed reactors (FBRs). Among them, the loop reactors are used to produce homopolypropylene, ethylene−propylene random copolymer, and ethylene−propylene−1-butene copolymer, and the FBR is used to produce impact polypropylene. , It is well acknowledged that the loop reactor is one of the best choices for the preparation of homopolypropylene due to its high mixing capability as well as high heat transfer/exchange rate …”
Section: Introductionmentioning
confidence: 99%
“…The Sanchez−Lacombe equation of state (S−L-EoS) was employed for the thermodynamic properties and the phase equilibrium calculations in the process units . As a whole, there are many methodologies proposed in the literature, which succeed in developing a comprehensive model for polyolefin processes. These methodologies include model selection and parameter tuning for physical and thermodynamic properties, catalyst characterization, and polymer properties in addition to the single and multiple site of traditional Ziegler−Natta polymerization kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies demonstrated that DArT markers showed characteristic of a single locus and tended to distributing in gene-rich regions of chromosomes compared to AFLP, RFLP and SSR markers in hexaploid wheat (Jaccoud et al, 2001, Semagn et al, 2006Peleg et al, 2008;Hong et al, 2009). Genetic mapping and QTLs detection were conducted using DArT markers by researchers (Semagn et al, 2006;Li et al, 2008;Mantovani et al, 2008;Peleg et al, 2008) as well as our present study, by which and some SSR markers, we constructed a map and identified four major QTL of dough rheological traits locating in the interval of WPT-8832-WPT-1675 on chromosome 1B.…”
Section: Discussionmentioning
confidence: 98%
“…The multi-layer penetration signals of the sensor are highly recognizable, and the processing circuit only needs simple processing to identify them [16] , and the dynamic test results are shown in Figure 2. Hong Yang of Beijing University of Technology used magnetoelectric velocity sensors to detect the information of velocity drop of intruding hard targets, so as to solve the problem of serious sticking and overlapping of projectile penetration overload signals due to the complexity of mechanical mechanism and sensitive system in the penetration process, which is difficult to identify [17] , and the results of multiple impact simulation tests in the laboratory are shown in Figure 3. The above new principles and structures of penetration sensors based on mechanical and non-mechanical principles to acquire penetration signals still have many technical problems to be solved, and not many have been applied in engineering yet.…”
Section: Layer Counting Detonationmentioning
confidence: 99%